Pyrolysis of Coconut Coir and Shell as Alternative Energy Source - sa'diyah, khalimatus; Rohman, Fatchur; Harsanti, Winda; Nugraha, Ivan; Febrianto, Nur Ahmad (Universitas Negeri Semarang, 2018)
Biomass waste can be used as raw material for bio-oil manufacture. One of the biomass is coconut coir and shell waste, commonly used as a substitute for firewood and handicraft materials. Therefore it takes effort to use coconut coir and shell to increase its economic value. One of the waste processing efforts is through pyrolysis process. Pyrolysis is the heating process of a substance in the absence of oxygen and produces products of solids, liquids and gases. The product of pyrolysis liquid is called bio-oil which can be used as alternative energy source. In this study, coconut coir and shell was pyrolysed as bio-oil. It also studied pyrolysis operating temperature and the amount of yield of bio-oil produced. The pyrolysis process was carried out in a reactor with a pressure of 1 atm and a varying operating temperature of 150 °C, 200 °C and 250 °C for 60 minutes. The reactor was equipped with a condenser as a cooling column. The mass of raw materials used was 500 grams with a size of 0.63 mm. The results of the research show that the higher the temperature, the more volume of bio-oil produced. For coconut coir pyrolysis it was obtained the highest yield of 34.2%, with density of 1.001 g/ml and viscosity of 1.351 cSt. As for coconut shell pyrolysis it was obtained highest yield of 45,2% with density of 1,212 g/ml and viscosity of 1.457 cSt. From the result of analysis using FTIR, the functional group of bio-oil was the most compound of phenol and alkene.